[Discussion of Capital Market Equilibrium, Information Production, and Selecting Accounting Techniques: Theoretical Framework and Review of Empirical Work]: A Reply - Gonedes, Nicholas J.; Dopuch, Nicholas (Journal of Accounting Research, 1974)
Nicholas J. Gonedes, Nicholas Dopuch, [Discussion of Capital Market Equilibrium, Information Production, and Selecting Accounting Techniques: Theoretical Framework and Review of Empirical Work]: A Reply, Journal of Accounting Research, Vol. 12, Studies on Financial Accounting Objectives: 1974 (1974), pp. 158-169